Peran Gadget dalam Meningkatkan Efektivitas Bisnis Mahasiswa Ekonomi Syariah Stain Bengkalis - Dzikrian Muarif; Syahrul Ramdani; Zuriatri putri; Titin Sumarni (Jurnal Strategi Bisnis Teknologi, 2024)
The development of information technology, especially through gadgets, has changed the business landscape significantly, even among students. This study aims to investigate the role of gadgets in increasing the business effectiveness of students majoring in Sharia Economics at STAIN Bengkalis. Qualitative research methods were used to gain a deeper understanding of how gadgets influence student business practices. The research results show that gadgets make a major contribution to increasing student business effectiveness. By using gadgets, students can access real-time market information, facilitate communication with clients and business partners, and optimize time management and productivity. Apart from that, gadgets are also an important tool in developing business networks and promoting products or services. These findings highlight the importance of integrating technology in Sharia Economics education to prepare students to face business challenges and opportunities in the digital era.